Prosedur Ekspor Albasia Bare Core oleh PT. Rejeki Pulau Samudera Logistik Melalui Pelabuhan Tanjung Emas Semarang - Supartini Supartini; Muhammad Adi Fachruli (Majalah Ilmiah Bahari Jogja, 2023)
In export activities, a shipping expedition company has a role in managing main documents, transportation, picking up empty containers, bringing them to the shipper and continuing until placing the containers in the container yard (CY). By using a qualitative method, this study analyzes the export procedures of Albasia Bare Core carried out by PT. Ocean Logistics Island Fortune. Data obtained through direct observation in the field, interviews and documentation. The study showed that the export procedures carried out by PT. Rejeki Pulau Samudera Logistics as a company engaged in a shipping expedition has been running well according to the Standard Operating Procedure set by the company. In handling the export of Albasia Bare Core, PT. Ocean Logistics Island Rejeki played important roles in managing export documents and transportation and also facilitating exporters to send goods abroad.